A Diary Study of Task Switching and Interruptions - Czerwinski, Mary; Horvitz, Eric; Wilhite, Susan (In Proceedings of the SIGCHI Conference on Human Factors in Computing Systems (CHI ’04), 2004)
We report on a diary study of the activities of information workers aimed at characterizing how people interleave multiple tasks amidst interruptions. The week-long study revealed the type and complexity of activities performed, the nature of the interruptions experienced, and the difficulty of shifting among numerous tasks. We present key findings from the diary study and discuss implications of the findings. Finally, we describe promising directions in the design of software tools for task management, motivated by the findings.